2010
DOI: 10.1007/s11418-010-0467-9
|View full text |Cite
|
Sign up to set email alerts
|

The potential benefits of a garlic and hydrochlorothiazide combination as antihypertensive and cardioprotective in rats

Abstract: The purpose of the present study was to investigate the protective effects of combined therapy of garlic homogenate and hydrochlorothiazide (HCTZ) in animals with hypertension and myocardial damage. Three weeks of high fructose (10% w/v) in fluid to albino rats resulted in hypertension. They were subsequently administered garlic (125, 250 and 500 mg/kg, 3 weeks in separate groups) and HCTZ (10 mg/kg, 6th week) once daily in their respective groups. At the end of 6 weeks, myocardial damage was induced by subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…In the present study, a fructose rich diet was used for the induction of diabetes, which is characterized by insulin resistance and metabolic syndrome very much similar to human type 2 diabetes mellitus. Previous studies have shown that longterm fructose feeding induces diabetes associated with insulin resistance and metabolic syndrome in experimental animals such as rats and mice [16,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a fructose rich diet was used for the induction of diabetes, which is characterized by insulin resistance and metabolic syndrome very much similar to human type 2 diabetes mellitus. Previous studies have shown that longterm fructose feeding induces diabetes associated with insulin resistance and metabolic syndrome in experimental animals such as rats and mice [16,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a fructose rich diet was used for the induction of diabetes, which is characterized by insulin resistance and metabolic syndrome very much similar to human type 2 diabetes mellitus. Previous studies have shown that long-term fructose feeding induces diabetes associated with insulin resistance and metabolic syndrome in experimental animals such as rats and mice [16,24-27]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, combination of SACS and CAP exerted super-additive (synergistic) interaction with respect to fall in blood pressure and angiotensin-converting enzyme inhibition. They also found that garlic in moderate dose (250 mg/kg) with added HCTZ possessed synergistic cardioprotective and antihypertensive properties against fructose-and isoproterenolinduced toxicities in albino rats (Asdaq and Inamdar 2011b ). They also reported that the bioavailability and half-life of propranolol were signifi cantly enhanced by two-and threefold, respectively, in animals pretreated with 250 mg/ kg garlic homogenate (Asdaq and Inamdar 2011a ).…”
Section: Animal Studiesmentioning
confidence: 95%